Assessment of early response to neoadjuvant chemotherapy in multi-site high-grade serous ovarian cancer using hyperpolarized-13C MRI - Lucian Beer; Vlad Bura; Stephan Ursprung; Ramona Woitek; Mary A. McLean; Joo Ern Ang; Mercedes Jimenez-Linan; Andrew B. Gill; Joshua Kaggie; Matthew Locke; Amy Frary; Johanna Field-Rayner; et al. (EJNMMI Research)
Abstract Background To evaluate the capability of hyperpolarized [1-13C] pyruvate MRI to predict pathologic response to neoadjuvant treatment in multi-site abdominopelvic disease of high-grade serous ovarian cancer (HGSOC) patients and to compare 13C MRI and [18F]-FDG PET/CT measurements for detecting early treatment response. We recruited eight patients with HGSOC in this prospective study who underwent 13C MRI and [18F]-FDG PET/CT before and after the first cycle of neoadjuvant chemotherapy treatment (NACT). Imaging parameters were compared with clinical and histophatologic parameters. Results We demonstrate here that 13C MRI of hyperpolarized [1-13C]pyruvate metabolism in multiple abdominal metastases resulted in rapid labeling of the endogenous tumor lactate pool. The rate of labeling was similar between the different anatomical disease sites and independent of tumor volume. The apparent rate constant describing exchange of 13C label between pyruvate and lactate (k PL) was positively correlated with PET standard uptake values (SUVmax) for [18F]-FDG in metastatic tumor deposits in the ovary/pelvis (R = 0.471, P = 0.02). Decreased lactate labeling could be detected after the first cycle of neoadjuvant chemotherapy and was associated with pathological response. There was no overall decrease in lactate labeling in a single patient who lacked a complete histopathologic response. k PL was associated with cancer tissue LDHA concentration (rho = 0.641; P = 0.02). Conclusion This exploratory study demonstrates the potential of 13C MRI measurements for assessing early response to neoadjuvant chemotherapy in patients with HGSOC.